HUBUNGAN DINAMIKA KELOMPOK TERHADAP TINGKAT ADOPSI INOVASI TEKNOLOGI PAKAN BUATAN PADA POKDAKAN MINA LESTARI KELURAHAN BANTUAS KECAMATAN PALARAN KOTA SAMARINDA - Is Apriansyah; Qoriah Saleha; Dayang Diah Fidhiani (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
This research aim is to know Mina Lestari group members characteristic, to know group dynamic level, to know adoption level of artificial feeding technology innovation and to know characteristic correlation with innovation adoption stage also to know group dynamic correlation toward adoption level of artificial feeding. Sampling method used is purposive sampling method with total respondent of 9 people. Data analysis methods used are descriptive analysis method and quantitative analysis with Rank Spearman correlation statistic test. Research result of Mina Lestari group members characteristic are observed by age who are dominant on 44-55 years old, formal education are Elementary School and Senior High School, Non-formal education of respondent majority are they do not ever join training, time of dominant fish farming have experience of 4-6 years, majority membership period in group are 5-6 years, and joining motivation on majority respondent because of their own willingness. Commulatively dynamic level of Mina Lestari group is categorized as high with score value of 64,11. Commulatively the adoption level of Mina Lestari feeding technology innovation is categorized medium with score value of 32,78. There are significant correlation between Mina Lestari group members characteristic on age indicator with conciousness, there are very significant correlation between formal education with conciousness stage and significant correlation between non-formal education with trial stage. There are significant correlation between Mina Lestari group dynamic toward adoption level on function indicator and group assignment with assessment stage and very significant correlation between group fish farming indicator with implementation stage.